WAR AND MARRIAGE IN HEINRICH BOLL - Kirmizi, Bulent (Selcuk Univ, Fac Letters, 2017)
This work on war and marriage in the post-war German novel attempted to reveal how Heinrich Boll influenced the destruction caused by the war in his works. When literature is handled periodically, it can be seen that every movement in the novel tradition runs parallel to its own axis of conflict. The event mesh also forms around this axis. As a background on the axis of the battle theme marriage, hunger, disease, etc. Many more have been the subject of novels. Although the study is not a sociological study, it has been shown that the concepts of human relations, family and marriage corresponded to the conditions of the day in German society by using the novels of Boll as a database. The structure of the work was structured in such a way as to emphasize the themes of war and family, the changes that took place with the war and the effects of these changes on the individuals. Having gained momentum for the growth and development of post-war German literature, Heinrich Boll has mirrored the period society structure in the character of his characters.
Keywords: Heinrich Boll; German literature; marriage and war